All Days 2009
DOI: 10.2118/123007-ms
|View full text |Cite
|
Sign up to set email alerts
|

New Product for Inhibition of Calcium Carbonate Scale in Natural Gas and Oil Facilities Based on Aloe Vera: Application in Venezuelan Oilfields

Abstract: Scales are secondary deposits constituted by inorganic chemical compounds present in an anthropogenic system. They are generated by changes in the thermodynamic, kinetic and hydrodynamics conditions[1] when formation fluids are produced, or by mutual physicochemical incompatibility between production and injection fluids. Therefore, they can jeopardize the integrity, good condition and useful lifetime of geological formations, producing and injection wells, surface facilities and pipelines, increasing the indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…Castillo et al . reported the inhibition results of calcium carbonate scale performed with Aloe Vera in Venezuelan oilfields (Castillo et al ., 2009).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Castillo et al . reported the inhibition results of calcium carbonate scale performed with Aloe Vera in Venezuelan oilfields (Castillo et al ., 2009).…”
Section: Resultsmentioning
confidence: 99%
“…In this respect, polyphenols or polysaccharides, which have hydroxyl and/ or carboxyl functional groups that interact with divalent ions such as Ca 2+ or Mg 2+ , are very good candidates. Castillo et al reported the inhibition results of calcium carbonate scale performed with Aloe Vera in Venezuelan oilfields (Castillo et al, 2009). Abdel-Gaber et al (2012) studied the antiscaling properties of Punica granatum hull and leaf extract in alkaline brine at 25°C.…”
Section: Mechanism Of Inhibition Of Cacomentioning
confidence: 99%
See 2 more Smart Citations
“…Aragonite or vaterite, also a form of CaCO 3 , is thermodynamically less stable than calcite. The antiscaling performance of calcite is more than that of the other states [126].…”
Section: Calcium Carbonatementioning
confidence: 90%